PENGARUH BESAR ALIRAN GAS TERHADAP CACAT POROSITAS DAN STRUKTUR MIKRO HASIL PENGELASAN MIG PADA PADUAN ALUMINIUM 5083 - Salahuddin Junus (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2011)
The amount of gas flow speed is a parameter of classification that can affect the quality of results of the classification and structure of the micro. One of the functional use of protective gas to protect the molten metal (weld pool) of elements in atmosfer. The use of high-speed gas flow is used to examine the influence of gas flow to the disabled porosity that occurred in the classification of MIG on aluminum alloy 5083. There are three variations gas flow speed is used to examine the influence of impaired quality of welded porosity that occurred in the classification of MIG. Test results obtained by the largest defect porosity occur at the speed of gas flow 12 liters/minute with a density of 2.2 g / cm ³ and the porosity as much as 46% with the lowest value of pull strength 51.150 MPa. Grants flow speed gas is an increasingly large number of particles of magnesium silicate (mg2si) and will mg2al3 reliability increased material, the content of zirconium (Zr) and some titanium (Ti) role as the resultant refiner details (grain-refiner), increased levels of refinement details with increasing heat input and speed welding. Keywords: aluminium welding 5083, gas flow, radiography test, penetran test, density, porosity, tensile strenght, micro structure